2020
DOI: 10.4251/wjgo.v12.i9.1031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcome of primary hepatic neuroendocrine tumors after comprehensive therapy

Abstract: BACKGROUND Primary hepatic neuroendocrine tumors (PHNETs), a group of neuroendocrine neoplasms, are extremely rare. There are only few case reports about PHNETs in the literature. The lack of large samples and multicenter research results in poor diagnostic and therapeutic approaches. AIM To discuss the clinical characteristics, diagnosis, and treatment of PHNETs and risk factors related to survival. METHODS We retrospectively analyzed the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Both CA19-9 and CA-125 are commonly used serum tumor markers for the preoperative diagnosis of cholangiocarcinoma [ 8 ]. However, Wang et al [ 9 ] reported that the positivity of CA19-9 was only 15.0%, CA72-4 was 7.5%, CEA was 17.5%, and AFP was 15.0% in primary hepatic neuroendocrine tumors. Furthermore, serum tumor markers are normal in most EBNET G1/G2, but they tend to be higher than normal levels in EBNET G3 or extrahepatic biliary neuroendocrine carcinomas [ 10 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both CA19-9 and CA-125 are commonly used serum tumor markers for the preoperative diagnosis of cholangiocarcinoma [ 8 ]. However, Wang et al [ 9 ] reported that the positivity of CA19-9 was only 15.0%, CA72-4 was 7.5%, CEA was 17.5%, and AFP was 15.0% in primary hepatic neuroendocrine tumors. Furthermore, serum tumor markers are normal in most EBNET G1/G2, but they tend to be higher than normal levels in EBNET G3 or extrahepatic biliary neuroendocrine carcinomas [ 10 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the mitotic index and Ki-67 index are of great value in evaluating the malignancy of PHNEN and its prognosis [18] . Wang et al [19] analysed the survival of 40 PHNET patients and found that the tumour grade and Ki-67 index were significantly related to the overall survival rate. Our case showed a low cell proliferation index, such as 2% Ki-67 and less than 2 mitoses in every 10 high-power fields.…”
Section: Discussionmentioning
confidence: 99%
“…3 , 14 , 15 TACE, platinum-based chemotherapy (EP/EC), radiofrequency ablation (RFA), and liver transplantation have been used to treat PHNEC in previous cases. 3 , 6 , 11 , 16–18 However, a systematic analysis of the treatment outcomes and prognostic factors in patients with PHNEC has not been conducted. In our study, 23 patients with advanced PHNEC received EP/EC, and 18 patients received TACE treatment.…”
Section: Discussionmentioning
confidence: 99%